Rehabilitation of devalued architectural heritage. What method and what is the result of the rehabilitation operation of the CREPS of Séraid? - MEBIROUK, Hayet (Journal of Human Sciences, 2020)
In Algeria, the critical state of built heritage has prompted interest in safeguarding it through the implementing of a rehabilitation policy. In this context, an expertise operation was launched by the CTC-Est concerning any building dating back to the 19th century and antiquity, although priority was given to the Regional Center for Physical and Sports Education (CREPS) in Séraidi . In 2002/2003, a first experiment in requalifying the infrastructure was launched, which ended in failure. From 2011, the rehabilitation works were relaunched and some blocks were already repaired. So, our goal is to examine the operation to rehabilitate this heritage. knowing that some current methods are reduced to technical repair solutions without detailed knowledge of the building and its circumstances? To achieve this objective, the preferred diagnostic analysis method to obtain information on the state of the building and the feasibility of the operation.